Variability of meteorological drought and some consequences on date palm cultivation in Biskra (Algeria) - Faci, Mohammed (2021)
Climate change threatens Algeria, like most countries in the world. This change accelerates and intensifies all climatic phenomena, causing extreme weather events. Drought, or water deficit, has a brutal impact on various aspects of life, whether ecological, environmental or economic, hence the need to analyze this natural phenomenon. In this context, this paper aims to analyze the meteorological drought in Biskra, south-east of Algeria, using five indices of drought: i) Rainfall Index, ii) Mean Deviation Index, iii) Standard Deviation Number Method, iv) Frequency Analysis, v) Standardized Precipitation Index. In general, the results obtained show a higher trend of dry years, despite the interannual variability between dry and wet years, with the recording of a drought sequence of five consecutive years. While the wet sequences did not exceed the three successive years. This variation, if associated with the lack of irrigation water and high temperatures, could reduce the quality and yields of dates, specifically 'Deglet Nour', which is a sensitive and demanding variety